Majorque et Trinacrie, deux branches de la dynastie d’Aragon, royautés composites et mondes des contacts - Henri Bresc (E-Spania)
The kingdoms of Mallorca and Trinacria (an artificial name given in 1302 to insular Sicily to distinguish it from the Angevin kingdom) have similar characteristics: these artificial states, cut out in a larger space, where they occupy peripheries, governed by branches of the dynasty of the kings of Aragon, and who continue to live in symbiosis with the Aragonese lineage, have in common that they are governed by artificial teams united by personal fidelity to the prince. Their common demographic weakness and the dangers that threaten them (respectively for Majorca, Aragon, but also Capetian France, and Naples, but also the great Aragonese brother for Sicily) led the two states to favor the economic initiative and inventiveness, enabling them to increase their tax revenues and thereby acquire military forces that have allowed for precarious survival